Conceptions of geography and history as school disciplines: an approach from lexical availability - de la Montaña Conchiña, Juan Luis; de la Maya Retamar, Guadalupe; López-Pérez, Magdalena (Frontiers in Psychology, 2023)
This paper aims to examine students’ conceptions of Geography and History as school disciplines at different educational stages. The sample, composed by a total of 73 participants from Primary School (n = 26), Secondary School (n = 29) and Higher Education (n = 18), completed a lexical availability test in Spanish and English or in Spanish and French. The results show that lexical availability increases as the educational stage increases, although the differences are not significant between all of them. The available lexical items on Geography and History, most of which are not shared between the different stages, are very generalist, showing a rigid and formal view of the disciplines. After the analysis carried out, we consider that lexical availability may constitute a valid tool for accessing students’ conceptions.